Hepatitis A: Leading Cause of Paediatric Acute Liver Failure in Bangladesh - Rashid, Rafia; Karim, ASM Bazlul; Islam, Fahmida; Mahmud, Salahuddin; Anwar, Sk Serjina (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Pediatric acute liver failure (PALF) is a multisystem disorder that gives rise to severe liver failure within days or weeks and occurs in children without pre-existing chronic liver disease. The etiology of PALF varies with age group and geographical area. Objectives: This study was aimed to evaluate the etiological factors of PALF in Bangladeshi children. Methods: This observational study was conducted at the Department of Paediatric Gastroenterology & Nutrition, Bangabandhu Sheikh Mujib Medical University, Bangladesh, from 2017 to 2020. Twenty-six PALF patients were included, purposively, excluding the acute-on chronic liver failure cases. Demographic data, vaccination history, and other information regarding etiology and complications were recorded. During hospital stay following investigations were performed: Serum bilirubin, liver enzymes, prothrombin time, serum albumin, serum creatinine and electrolytes. Fisher’s exact test determined the association between etiologies of PALF and past histories along with other descriptive statistics using the open-source PSPP software. Results: The average age of the 26 studied patients was 8.6±3.5 years, and 73.1% belonged to 5-12 years of age group. Half of the patients had a history of taking street food or unsafe water. Only six patients had a history of ingestion of herbal medicine. None of the patients had history of vaccination against Hepatitis A. The etiology of PALF patients varied. About 54% of the studied patients had HAV infection, in 23.1% etiology was not determined. About 71.4% of the study patients with HAV infection had a history of taking street food or unsafe water, and this association was statistically significant. Conclusion: This study found that hepatitis A virus infection is the leading cause of paediatric acute liver failure in Bangladesh. Timely preventive measures may help in lowering fatality from liver diseases in children in Bangladesh. DS (Child) H J 2021; 37(2): 93-97